Design of Internet of Things (IoT) Based Hydroponic Controlling Device in Pyramid Greenhouse - Arif Umami; Bagus Muhammad Akbar (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
Smart farming technology was previously implemented at Wedomartani experimental station, Faculty of Agriculture UPN